Combined source-channel coding schemes for video transmission over an additive white Gaussian noise channel - Bystrom, M.; Modestino, J.W. (IEEE journal on selected areas in communications, 2000)
There has been an increased interest in the transmission of digital video over real-world transmission media, such as the direct broadcast satellite (DBS) channel. Video transmitted over such a channel is subject to degradation due, in part, to additive white Gaussian noise (AWGN). Some form of forward error-control (FEC) coding may be applied in order to reduce the effect of the noise on the transmitted bitstream; however, determination of the appropriate level of FEC coding is generally an unwieldy and computationally intensive problem, as it may depend upon a variety of parameters such as the type of video, the available bandwidth, and the channel SNR. More specifically, a combined source-channel coding approach is necessary in optimally allocating rate between source and channel coding subject to a fixed constraint on overall transmission bandwidth. In this paper we develop a method of optimal bit allocation under the assumption that the distortion is additive and independent on a frame-by-frame basis. A set of universal operational distortion-rate characteristics is developed which balances the tradeoff between source coding accuracy and channel error protection for a fixed overall transmission rate and provides the basis for the optimal bit allocation approach. The results for specific source and channel coding schemes show marked improvement over suboptimum choices of channel error protection. In addition, we show that our results approach information-theoretic performance bounds which are developed in this work.